Geloofsgroei by Paulus? - Pelser, G. M. M. (Hervormde teologiese studies, 1985)
In this essay the question is posed as to whether Paul viewed faith as essentially an entity that can grow or increase within the believer or is given by God in different degrees to different people. The investigation is limited to Rm 12:3; 14:1; 2 Cor 10:15; Phlp 1:25 and 1 Th 3:10. The conclusion is reached that as far as these passages are concerned, the answer to the question is negative, with the possible exception of 2 Cor 10:15. It seems therefore that according to Paul, faith is faith, nothing less and nothing more. In so far, however, as there is mention in Paul of growth connected with faith, it concerns the believer's answer to the imperative in the indicative by living up daily (and increasingly) to his faith. Essentially faith cannot be weak or mediocre. If this should be the case, it is not faith any more.